If it's not what You are looking for type in the equation solver your own equation and let us solve it.
81=-3(-3v-3)
We move all terms to the left:
81-(-3(-3v-3))=0
We calculate terms in parentheses: -(-3(-3v-3)), so:We get rid of parentheses
-3(-3v-3)
We multiply parentheses
9v+9
Back to the equation:
-(9v+9)
-9v-9+81=0
We add all the numbers together, and all the variables
-9v+72=0
We move all terms containing v to the left, all other terms to the right
-9v=-72
v=-72/-9
v=+8
| 8=πd | | 7+6p=7p-3 | | -y+13*49=-40 | | 8=4(r+) | | 11(e-11)+12=1 | | 3(x-4)-5(2x+1)=-4 | | -49*y+13=-40 | | -4(r+3)=-75 | | -49•y+13=-40 | | 2.7+x=23 | | -x-3x=3-x-6x | | 7/x+1/2=-3 | | 3(p+1)-2p=6p+23 | | 3=(5x-2)=69 | | -h-2-7h=10h-10 | | 2(x-5)-3(2-2x)=10 | | 6h+8h=11+5+5+2 | | |2m+7|-9=1 | | x2.4=8.3 | | 8r-7+5r=2r-3 | | 2.3x=1/2 | | 13x=12*18 | | -2(3y-3)+9y=7+2(6y-8) | | 13x=12(18) | | X2+3x-0=300 | | 2+8-z=24 | | (12/13)=(x/18) | | 9x-4x+x=36 | | 2.3e-6.2=3.8-3.7e | | 13+2t=27 | | 5-3/4(4x+14)=-3x-15 | | X/2-3=4x-38 |